Respuesta :

Answer:

x^4- x^3- 4x^2-3

Step-by-step explanation:

Given

f(x)= x^4- x^2+9

And

g(x)= x^(3 )+ 3x^2+12

We have to find

(f-g)(x)= ?

The operations on functions are as easy as the operations on numbers or polynomials.

We have to subtract the functions to find the above mentioned operation.

=(f-g)(x)=f(x)-g(x)

(f-g)(x)=[x^4- x^2+9]-[x^(3 )+ 3x^2+12]

The minus will change the signs of function g.

= x^4- x^2+9- x^(3 )- 3x^2-12

= x^4- x^3- x^2- 3x^2+9-12

=x^4- x^3- 4x^2-3

lemion

Answer:

[tex]x^4-x^3-4x^2-3[/tex]

Step-by-step explanation:

Ver imagen lemion